Isocoumarin formation by heterologous gene expression and modification by host enzymes - Xiang, Pan; Ludwig-Radtke, Lena; Yin, Wen-Bing; Li, Shu-Ming (Organic & biomolecular chemistry, 2020)
Heterologous expression has been proven to be a successful strategy for the identification of metabolites encoded by cryptic/silent genes. Expression of a nonreducing polyketide synthase (NR-PKS) gene from Penicillium crustosum in Aspergillus nidulans led to the accumulation of three isocoumarins 1-3 . Feeding experiments revealed that the PKS product 1 can be converted by the host enzymes to its hydroxylated ( 2 ) and methylated ( 3 ) derivatives. These results provided one additional example that unexpected further modifications of an enzyme product can take place in a heterologous host. The polyketide synthase product was converted to its methylated and hydroxylated derivatives by host endogenous enzymes.